1986
DOI: 10.1152/ajpheart.1986.250.4.h558
|View full text |Cite
|
Sign up to set email alerts
|

Role of adenosine in coronary autoregulation

Abstract: The role of cardiac interstitial adenosine as an important metabolite in coronary autoregulation has not been established. We therefore measured steady-state cardiac interstitial adenosine concentration at a high and a low coronary inflow pressure using an epicardial diffusion well in anesthetized dogs. Although coronary resistance for the high and low pressure points showed highly significant differences (P less than 0.001), adenosine averaged 302 +/- 98 and 286 +/- 91 (SD) pmol/ml for the high and low pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Previous studies have demonstrated that endogenous adenosine is not obligatory for maintaining coronary blood flow during normal arterial inflow. Thus, studies in anesthetized open-chest dogs (15)(16)(17)(18)(19) and awake dogs (1,20) failed to demonstrate an effect of intracoronary adenosine deaminase (15)(16)(17), or adenosine receptor blockade with intravenous aminophylline (18, 19) or 8-phenyltheophylline (1, 20), on (21) examined the effect of exercise on myocardial adenosine production. They found that treadmill exercise in dogs resulted in a fivefold increase in myocardial adenosine content, with a doubling of the coronary arterio-venous adenosine content difference.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that endogenous adenosine is not obligatory for maintaining coronary blood flow during normal arterial inflow. Thus, studies in anesthetized open-chest dogs (15)(16)(17)(18)(19) and awake dogs (1,20) failed to demonstrate an effect of intracoronary adenosine deaminase (15)(16)(17), or adenosine receptor blockade with intravenous aminophylline (18, 19) or 8-phenyltheophylline (1, 20), on (21) examined the effect of exercise on myocardial adenosine production. They found that treadmill exercise in dogs resulted in a fivefold increase in myocardial adenosine content, with a doubling of the coronary arterio-venous adenosine content difference.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that endogenous adenosine production is not obligatory for maintaining resting CBF. Thus, studies in anesthetized openchest dogs failed to demonstrate an effect of intracoronary adenosine deaminase (18)(19)(20) or intravenous aminophylline to block adenosine receptors (21,22), on basal CBF. Similarly, in awake dogs intracoronary adenosine deaminase or intravenous 8-phenyltheophylline, in doses that caused marked inhibition of exogenous adenosine-induced coronary vasodilation, had no effect on resting CBF (1,23 gated the role of KAT channels in maintaining resting CBF.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Dole et al 37 found that adenosine deaminase infused into the blood-perfused dog myocardium moderately reduced the magnitude of reactive hyperemia but did not significantly affect autoregulation. Hanley et al 38 also found that adenosine deaminase did not attenuate autoregulation the blood-perfused dog heart. Winn and co-workers 39 found adenosine levels in the rat brain increased as systemic arterial pressure was reduced, but the increase was statistically significant only at pressures below the autoregulatory range.…”
mentioning
confidence: 95%